The effects of fatigue on muscle synergies in the shoulders of baseball players - Thomas, S. J.; Castillo, G. C.; Topley, M.; Paul, R. W. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Muscle synergies are defined as the central nervous system`s organizational structure for movement. Muscle synergies change after muscular fatigue, with certain synergies assuming the primary role to compensate for fatigue within another muscle synergy. Owing to the high eccentric forces imposed upon the external rotators (ie, posterior rotator cuff), pitchers that continue to throw while fatigued are at a significantly higher risk of shoulder and/or elbow injury; however, the neuromuscular compensation strategies of baseball players in response to fatigue are currently unknown.